Managing the cultural pitfalls of hybrid work : the authors offer 11 strategies for leading more effective hybrid teams based on data from a recent survey of marketing leaders - Moorman, Christine; Hinkfuss, Katie (MIT Sloan Management Review, 2023)
Although the hybrid work model has been widely adopted among many businesses, the complications involving peer relationships and connections that it has introduced linger on. Relying on results from The CMO Survey, the authors derived a set of strategies to help leaders navigate organizational culture and the socialization of new employees during this era of digital transformation.